Diabetes and Cardiorenal Complications: A Clinical Review of Existing Therapies and Novel Combinations, Focusing on SGLT2 Inhibitors - Kale, Ajinath; Sharma, Anshima; Anders, Hans-Joachim; Gaikwad, Anil B. (Current Diabetes Reviews, 2023)
Type 2 diabetes mellitus (T2DM) is a set of metabolic disorders specified by hyperglycemia as a result of abnormalities in insulin secretion or sensitivity. Chronic kidney disease (CKD) and cardiovascular disease (CVD) are the widespread co-morbidities of T2DM and share risk factors for onset and progression. Despite numerous mono- and combination therapies exist, the progression of diabetes complications remains a global health concern. Treatment options for diabetic- CKD and CVD include drugs targeting hyperglycemia, hypertension, albuminuria, hyperlipidemia and the renin-angiotensin aldosterone system (RAAS). The sodium-glucose co-transporter 2 channel (SGLT2) is abundantly present in proximal tubules of the kidney and its capacity to recover glucose and sodium from the glomerular filtrate limits urinary glucose and sodium excretion. SGLT2 inhibitors (SGLT2i) reduce sodium and glucose reabsorption in the proximal and thus increase urinary glucose excretion in T2DM. SGLT2i monotherapy can improve but dual SGLT2/RAAS inhibition or SGLT2i along with other classes of drugs are more effective in protecting the kidneys and the cardiovascular system in patients with and without diabetes. Combinations such as empagliflozin and linagliptin, ertugliflozin and metolazone, dapagliflozin and sacubitril- valsartan and many more show promising results. Here, we have reviewed the ongoing and completed clinical trials, addressed current theories, and discussed necessary future research to explain the possible risks and benefits of using an SGLT2i alone and in combination with existing antidiabetic drugs and drugs acting on the cardiovascular system.
Keywords: SGLT2 inhibitors